CONTENTS (Medical Forum Monthly, 2024)
Postoperative Wound Infection After Midline Abdominal Incisions 2-5 Afzal Siddique 2. Malik Asrar AhmedSmoking Behavior among Medical and Dental Students in Abbottabad, Pakistan 6-9 Muhammad Usman Anjum 2. Rizwan Anwar 3. Muhammad Safdar Khan 4. Rawaha Ahmad 5. Syed Humayun ShahIncreasing Trend of Battered Wife in Pakistan 10-13 Alvina Raja 2. Azhar Masud Bhatti 3. Abid Karim 4. Abdul Hamid 5. NajeebEffects of Aerobic Exercise on Lipid Profile in Patients with Type 2 Diabetes (NIDDM) 14-17 Ghulam Murtaza Kaka 2. Mumtaz Ali Memon 3. Asmat Kamal AnsariCeliac Disease; A Hidden Cause of Iron Deficiency Anemia? 18-21 Rakhshinda Jabeen 2. Hussain Haroon 3. Fawad Qureshi 4. Syed Shirjeel Husain 5. Asma ZishanOutcomes of Fibrinolytics in Patients of Acute Myocardial Infarction 22-26 Mushtaq Ahmed 2. Abdul Wali 3. Amjad AliComparison of Felodipine and Propranolol in the Treatment of Hypertension 27-30 Noor-ul-huda Ansari 2. Mushtaq Ahmed 3. Abdul Jabbar 4. Abira Nazir 5. Nehal NaseerEffects of George Ohsawa One (Macrobiotic) on Biochemical and Haematological Parameters other than Prothrombin Time and Activated Partial Thromboplastin Time in Rabbits 31-35 Mohammad Ahmad Alamgir 2. Saadia Shahzad AlamImpact of Faculty Development Workshop on Faculty Performance - A Problem Based Learning Approach 36-39 Seyyedha Abbas 2. Naushaba Sadiq 3. Ayesha FarooqEffect of Aloe Vera Whole Leaf Extract on Lipid Profile Status in High Fat Diet and Low Dose Streptozotocin Induced Type 2 Diabetic Rats 40-44 Meena Gul 2. Muhammad Khalid 3. Nabila Sher MohammadEvaluation of Golden Proportion Between Maxillary Anterior Teeth 45-48 Asma Saher Ansari 2. Asmat Jameel 3. Amynah CharaniaTransabdominal and Transvaginal Repair of Vesicovaginal Fistula 49-51 Majeed Ullah Buzdar 2. M. Amjad Khan 3. Naz AkhtarComparison of In-Vitro Conditioning of Two Types of Mandibular Bone Plates in Modified Simulated Body Fluid Characterization with Scanning Electron Microscope and Energy Dispersive X-Ray Spectroscopy 52-55 Rabia Anwar 2. Muhammad Kaleem 3. Fahad Saqib LodhiSequential Organ Failure Assessment (SOFA) Score as a Predictor of Outcome in Patients Admitted in a Medical ICU 56-60 Adil Faraz 2. Muhammad Tanveer Alam 3. Muhammad Hussain HaroonAssess the Attitude and Practices of Pharmacists regarding Selling of Various Over-the-Counter Medicines in Mirpurkhas District 61-65 Marium Azfar 2. Nausheen Khawar 3. Isma Sajjad